Unraveling the link: exploring what risk factor for sleep disorders among paediatric migraine - Bei Wang; Liuyi Li; Shuyan Feng; Lin Yu; Shuman Feng (BMC Neurology)
Abstract Background Migraine is closely related to sleep disorders. Vitamin D is known to regulate sleep, cell proliferation and differentiation. The aim of our study was to measure the predictive value of vitamin D for sleep disorders in paediatric migraine. We hypothesized that vitamin D would be apredictor of sleep disorders in paediatric migraine. Methods We conducted an analysis of serum vitamin D levels in 150 paediatric migraine. The Pittsburgh Sleep Quality Index (PSQI) was used as a measure of sleep quality. Based on the PSQI scores, the subjects were divided into normal sleep group and sleep disorder group. Correlation analysis and regression analysis were employed to explore the potential etiology of sleep disturbances in paediatric migraine. Results There was significant difference in the prevalence of sleep disorders between paediatric migraine and the control group (Odds ratio [OR] = 4.91,95% confidence interval [CI] = 3.25–7.40, P = 0.001). Additionally, the regression analysis demonstrated that vitamin D could serve as a predictive factor for sleep disorders in paediatric migraine (OR = 0.008, 95%CI: 0.023–0.225, P = 0.004). The receiver operating characteristic (ROC) analysis revealed an area under the curve (AUC) of 0.957 (95% CI 0.925–0.988), with a cutoff value of 15.84 ng/ml, a sensitivity of 87.5%, and a specificity of 93.7% for serum vitamin D. Conclusion Our study confirms the association between sleep disorder and vitamin D levels in paediatric migraine. The use of vitamin D supplementation as a treatment strategy for sleep disturbances in paediatric migraine needs further investigation.